Adaptation and Implementation of Financial Education for Early Childhood in the Post-Pandemic Era: A Case Study in Yogyakarta - Nafiah, Qotrun Nada; Munastiwi, Erni (Jurnal Pendidikan Islam, 2023)
Purpose – This study aims to examine and understand financial education practice for early childhood in Yogyakarta during the post-pandemic era to gain new insights and knowledge relevant to the subject. Design/methods/approach – This research employs a qualitative and case study approach. Data was collected through structured interviews using WhatsApp and Zoom Meetings with 10 teachers from Raudhatul Athfal. Data analysis was based on Miles and Huberman’s data reduction, display, and verification technique. Findings – The findings indicate a significant change in financial education practice post-pandemic. The impact of remote learning on children's financial education, along with the efforts of teachers in planning, implementing, and evaluating financial education programs, has been identified. Teachers are crucial in implementing the student-centered learning approach to enhance financial literacy. Research implications – These findings provide important insights into the significance of the student-centered learning approach in financial education and the vital role of teachers as facilitators in the learning process. This study also emphasizes the need for ongoing evaluation and cooperation between teachers and parents in children's financial education. The results can contribute to developing policies and practices in financial education, particularly in the post-pandemic context, and open opportunities for further research in this field.